Impact of hypoxic tumor microenvironment and tumor cell plasticity on the expression of immune checkpoints. (28th August 2019) - Lequeux, Audrey; Noman, Muhammad Zaeem; Xiao, Malina; Sauvage, Delphine; Van Moer, Kris; Viry, Elodie; Bocci, Irene; Hasmim, Meriem; Bosseler, Manon; Berchem, Guy; Janji, Bassam
Abstract: Compared to traditional therapies, such as surgery, radio-chemotherapy, or targeted approaches, immunotherapies based on immune checkpoint blockers (ICBs) have revolutionized the treatment of cancer. Although ICBs have yielded long-lasting results and have improved patient survival, this success has been seriously challenged by clinical observations showing that only a small fraction of patients benefit from this revolutionary therapy and no benefit has been found in patients with highly aggressive tumors. Efforts are currently ongoing to identify factors that predict the response to ICB. Among the different predictive markers established so far, the expression levels of immune checkpoint genes have proven to be important biomarkers for informing treatment choices. Therefore, understanding the mechanisms involved in the regulation of immune checkpoints is a key element that will facilitate novel combination approaches and optimize patient outcome. In this review, we discuss the impact of hypoxia and tumor cell plasticity on immune checkpoint gene expression and provide insight into the therapeutic value of the EMT signature and the rationale for novel combination approaches to improve ICB therapy and maximize the benefits for patients with cancer. Highlights: Immune checkpoint blockade (ICB)-based cancer immunotherapies have revolutionized the treatment of cancer patients. There is an urgent clinical need to identify biomarkers predicting the response to ICB. The complex interplay between hypoxia and EMT modulates the expression of immune, checkpoints including PD-L1 and CD47. This review provides an extensive overview of the emerging concepts involved in immune checkpoint regulation.